Physicochemical, sensory, and nutritional quality of fresh-cut “Rojo Brillante” persimmon affected by maturity stage and antibrowning agents - Sanchís, Elena; Mateos, Milagros; Pérez-Gago, María B. (SAGE, 2020)
To prevent enzymatic browning of fresh-cut ‘Rojo Brillante’ persimmon, different combinations of ascorbic acid (AA) and citric acid (CA) with calcium chloride (CaCl2) were tested in fruit harvested at two maturity stages (MS1 and MS2). Color, firmness, sensory quality, total vitamin C, radical scavenging activity, total phenolic content, and carotenoids were evaluated over nine days of storage at 5 ℃. Antibrowning dips reduced enzymatic browning if compared with the control samples. Selecting fruits with good firmness and the addition of 10 g/l CaCl2 help prevent loss of firmness of fresh-cut “Rojo Brillante” persimmons treated with acidic solutions as antibrowning agents to control enzymatic browning. The limit of marketability of the persimmon fruit processed at MS1 was significantly reduced by the burst of the disorder known as “flesh browning,” and only the samples treated with 10 g/l CA + 10 g/l CaCl2 maintained a limit of marketability close to seven days. At MS2, all the antibrowning solutions allowed a limit of marketability of seven storage days at 5 ℃. Nutritional quality was not affected by either antibrowning dips or cutting processes, but MS at harvest was.